2020
DOI: 10.1088/2632-2153/aba9ef
|View full text |Cite
|
Sign up to set email alerts
|

Structure-property maps with Kernel principal covariates regression

Abstract: Data analyses based on linear methods constitute the simplest, most robust, and transparent approaches to the automatic processing of large amounts of data for building supervised or unsupervised machine learning models. Principal covariates regression (PCovR) is an underappreciated method that interpolates between principal component analysis and linear regression and can be used conveniently to reveal structure-property relations in terms of simple-to-interpret, low-dimensional maps. Here we provide a pedago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 49 publications
0
45
0
Order By: Relevance
“…Finally, by combining the structural information (from SOAP similarity, as used in Fig. 2g) and the machine-learned electronic fingerprints, we may construct structure-property maps for atomic environments using kernel principal covariates regression 47 . This approach yields 2D slices that map out the atomic environments, arranged so as to reflect structural diversity and also the relationship between structure and metallicity, for which the locally-averaged ML DOS(EF) is used as a proxy 42 .…”
Section: Electronic Fingerprints From Machine Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, by combining the structural information (from SOAP similarity, as used in Fig. 2g) and the machine-learned electronic fingerprints, we may construct structure-property maps for atomic environments using kernel principal covariates regression 47 . This approach yields 2D slices that map out the atomic environments, arranged so as to reflect structural diversity and also the relationship between structure and metallicity, for which the locally-averaged ML DOS(EF) is used as a proxy 42 .…”
Section: Electronic Fingerprints From Machine Learningmentioning
confidence: 99%
“…To this end, we use the recently-introduced kernel principal covariates regression (KPCovR) method, described in Ref. 47, that can be seen as a modified kernel principal-component analysis in which one uses a modified kernel with a scaling parameter, ,…”
Section: Dos( ) = � Ldos( )mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, methods based on metric learning 111,115 did not lead to any improvement, as the high dimensionality of the problem led to severe overtting. Ceriotti et al 116 suggested the use of principal covariates regression (PCovR) to solve similar issues. 117 PCovR is a supervised feature selection method that interpolates between principal component analysis (PCA) and linear regression.…”
Section: Molecular Representationsmentioning
confidence: 99%
“…Ceriotti et al 116 suggested the use of principal covariates regression (PCovR) to solve similar issues. 117 PCovR is a supervised feature selection method that interpolates between principal component analysis (PCA) and linear regression. Herein, because the variance of the features is completely unrelated to the importance scores, the addition of PCA would not offer any advantage.…”
Section: Molecular Representationsmentioning
confidence: 99%